A role for cancer‐associated fibroblasts in inducing the epithelial‐to‐mesenchymal transition in human tongue squamous cell carcinoma. (20th March 2014) - Zhou, Bin; Chen, Wei‐Liang; Wang, You‐Yuan; Lin, Zhao‐Yu; Zhang, Da‐Ming; Fan, Song; Li, Jin‐Song
<x xml:space="preserve">Abstract</x> Objectives Lymph node metastasis is a prominent clinical feature of tongue squamous cell carcinoma (TSCC) and is associated with a higher mortality rate. Carcinoma‐associated fibroblasts (CAFs), a major component of the tumor microenvironment (TME), play an important role in tumor progression, and are associated with a poor prognosis. The aim of this study was to examine the role of CAFs in promoting the invasion of TSCC through the epithelial‐to‐mesenchymal transition (EMT). Materials and Methods A series of matched CAF and normal fibroblast (NF) pairs were assessed for cell morphology and for the expression of alpha smooth muscle actin (α‐SMA), stromal cell‐derived factor‐1 (SDF1), fibroblast‐activating protein (FAP), vimentin, and cytokeratin (CK) markers. Transwell assays, Western blot analysis, reverse transcription‐PCR, and immunofluorescence staining were used to assess the role of CAFs, as compared to that of NFs, in promoting proliferation, migration, invasion, and EMT in TSCC. Results Both CAF and NF primary cultures expressed vimentin but not CK. CAFs showed significantly higher α‐SMA protein levels, SDF1 secretion, and mRNA levels of α‐SMA, SDF1, and FAP. We also found that co‐culture with CAFs enhanced the proliferation and invasion of SCC9 cells. Moreover, co‐culture with CAFs induced upregulation of the EMT markers fibronectin and vimentin, downregulation of E‐cadherin, and enhanced invasion in SCC9 cells. Conclusion These results suggest that CAFs induce EMT marker expression and functional changes in TSCCs.